Transformasi Budaya lslam di Kerajaan Bone pada Abad ke XVII - Rahmawati Rahmawati; Mohd. Azizuddin Mohd. Sani (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2016)
The purpose of this study is to analyze and also describe about the transformation of local culture towards Islamic culture at Bone Kingdom on 17th century. In cultural study, one of the most interesting objects to be known is to explore the form of culture when the integration process has been done. The study will be focused on Islamic culture, when Islam emerged at South Celebes on 13th until 17th century by our ulemas (Datu ri Bandang, Datu Patimang, and Datu ri Tiro), particularly at Bone region. On 17th century, Bone’s ruler gave some penetration to tackle Islam, spreading to their region (Bone still as an independent Kingdom). After musu assellenggeng or Islamic war, Bone’s ruler had accepted Islam as their religion.